2000
DOI: 10.1002/1529-0131(200003)43:3<628::aid-anr20>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-related proteins 8 and 14 are specifically secreted during interaction of phagocytes and activated endothelium and are useful markers for monitoring disease activity in pauciarticular-onset juvenile rheumatoid arthritis

Abstract: MRP8 and MRP14 are specifically released during the interaction of monocytes with inflammatory activated endothelium, probably at sites of local inflammation. Their serum concentrations represent a useful marker for monitoring local inflammation in JRA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
286
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 357 publications
(311 citation statements)
references
References 33 publications
18
286
1
1
Order By: Relevance
“…Two other S100 proteins, S100A8 and S100A9, were also found in high concentrations in patients with JRA, especially in those with therapy-refractory systemic-onset JRA (49)(50)(51). These proteins are more abundant and are not restricted to granulocytes, where they contribute to ϳ50% of the cytosolic protein.…”
Section: Discussionmentioning
confidence: 99%
“…Two other S100 proteins, S100A8 and S100A9, were also found in high concentrations in patients with JRA, especially in those with therapy-refractory systemic-onset JRA (49)(50)(51). These proteins are more abundant and are not restricted to granulocytes, where they contribute to ϳ50% of the cytosolic protein.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of mock-transfected CHO cells with a physiologically-relevant concentration of EN-RAGE, 4 10 g/ml, did not significantly increase intensity of the bands corresponding to phosphorylated MEK 1/2 or p44/42 MAP kinases [22][23] (Figure 4d,e, respectively; lanes 1-5). However, exposure of RAGE 82G CHO transfectants to EN-RAGE increased by 2.2-fold and 1.9-fold phosphorylated MEK 1/2 and p44/42 MAP kinases, compared with cultures incubated with BSA alone (P Ͻ 0.01; Figure 4d,e respectively; lanes 7 and 6).…”
Section: Rage 82s Allele Enhances Binding/signalling/gene Expression mentioning
confidence: 93%
“…1 S100/calgranulins, proinflammatory signal transduction ligands of the receptor, are enriched in joints of subjects with rheumatoid arthritis (RA). [2][3][4] Members of this family of molecules, long-associated with classic immune/ inflammatory disorders, 5,6 may be released by activated inflammatory effector cells such as monocytes, 7 thereby freeing them to engage cell surface RAGE and amplify host inflammatory responses. Indeed, accumulation of S100/calgranulins in synovial fluid and plasma of subjects with RA has been correlated with indices of disease severity, such as bony erosions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that the levels of MRP8 and 14 were elevated in juvenile RA and correlated with disease activity is in support for a role of EN-RAGEs in chronic inflammation. 11 It is in this context that the authors performed studies in a collagen-induced murine arthritis model, which demonstrated that blockade of RAGE suppressed clinical, molecular and histological evidence of arthritis, thereby supporting a functional role for RAGE in arthritis. 4 These findings made the RAGE gene an attractive candidate to study for the existence of allelic variations that might be important in the pathogenesis of inflammatory disease.…”
mentioning
confidence: 98%